Comparing Human Factors for Augmented Reality Supported Single-User and Collaborative Repair Operations of Industrial Robots - Aschenbrenner, Doris; Leutert, Florian; Çençen, Argun; Verlinden, Jouke; Schilling, Klaus; Latoschik, Marc; Lukosch, Stephan (Frontiers in Robotics and AI, 2019)
In order to support the decision-making process of industry on how to implement Augmented Reality (AR) in production, this article wants to provide guidance through a set of comparative user studies. The results are obtained from the feedback of 160 participants who performed the same repair task on a switch cabinet of an industrial robot. The studies compare several AR instruction applications on different display devices (head-mounted display, handheld tablet PC and projection-based spatial AR) with baseline conditions (paper instructions and phone support), both in a single-user and a collaborative setting. Next to insights on the performance of the individual device types for the single mode operation, the study is able to show significant indications on AR techniques are being especially helpful in a collaborative setting.